2003
DOI: 10.1021/ja0381398
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Surface Species Formed on Au/TiO2 during the Reaction of H2 and O2:  An Inelastic Neutron Scattering Study

Abstract: Inelastic neutron spectroscopy (INS) has been employed to identify surface species formed during the H2-O2 reaction on Au/TiO2 catalysts. Determination of the surface intermediates formed in this reaction is crucial to develop a mechanistic understanding for the direct vapor-phase propylene epoxidation reaction and synthesis of H2O2. Although the presence of intermediate hydroperoxo species (during these reactions) has been suggested in literature, it has never been demonstrated. Our studies provide direct evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 17 publications
6
124
1
1
Order By: Relevance
“…They also registered the presence of water molecules on the Au surface, which is consistent with the fact that H 2 O 2 readily decomposes to water unless an acid or surface protons are present to stabilize it. [18] Thus, they concluded that the observed hydroperoxo radical must be either bound to Au or complexed with water resulting from decomposition of H 2 O 2 . Figure 4 provides further evidence for the different behavior of the two films toward detection of the two gases.…”
Section: àmentioning
confidence: 99%
See 2 more Smart Citations
“…They also registered the presence of water molecules on the Au surface, which is consistent with the fact that H 2 O 2 readily decomposes to water unless an acid or surface protons are present to stabilize it. [18] Thus, they concluded that the observed hydroperoxo radical must be either bound to Au or complexed with water resulting from decomposition of H 2 O 2 . Figure 4 provides further evidence for the different behavior of the two films toward detection of the two gases.…”
Section: àmentioning
confidence: 99%
“…[12][13][14][15][16][17] Despite this, a number of authors report studies on the nature of adsorbed species over the TiO 2 -Au systems during reaction of H 2 and O 2 . [18,19] It was demonstrated that on nanosized Au clusters, hydrogen and oxygen react to form one or more hydrogen peroxide and surface hydroperoxy species. [8,[18][19][20][21] At operative temperatures in the 250-300 8C range they found evidence for formation of H 2 O 2 and of a hydroperoxo radical on the Au NP surface, where the latter is likely to form a hydrogen bonded complex with water or bind directly to the oxide surface.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold-titania catalysts can epoxidize propene in the presence of a mixture of hydrogen and oxygen under very mild conditions (323-373 K and atmospheric pressure). The fact that both hydrogen and oxygen are needed for this oxidation reaction has triggered speculation that a peroxide species would be an important reaction intermediate for the oxidation, 2,8,9 which is supported by the fact that titania is capable of epoxidizing propene using hydrogen peroxide in the liquid phase, 10 and the fact that gold has been observed to produce hydrogen peroxide directly from hydrogen and oxygen.11 Although these gold-titania epoxidation catalysts are highly selective, they have two main problems that need to be addressed. The conversion remains quite low (typically below 2%, although conversions of up to 10% have been reported with certain promoters 12 ) and the hydrogen efficiency is insufficient, 3 typically 30%.…”
mentioning
confidence: 99%
“…Most of their results were recently confirmed using modern spectroscopy techniques (Sivadinarayana et al, 2004, Chinta andLunsford, 2004). The fact that O-O bond does not dissociate during H 2 O 2 formation was experimentally confirmed by Dissanayake and Lunsford, 2003, and the presence of HO 2 -on catalyst surface during the reaction was discovered by Sivadinarayana et al, 2004. In the recent decade, much work has been done to investigate in greater detail the effect of various parameters on the DC reaction. The group of Choudhary demonstrated the effect of the nature and concentration of acid and halide promoters on reactions (1), (2) and (3), as well as the effect of the oxidation state of palladium (Choudhary and Samanta, 2006;Samanta and Choudhary, 2007a;Choudhary et al, 2006aChoudhary et al, , 2007.…”
Section: Iii3 Kinetics Of Synthesis Reactionmentioning
confidence: 85%